(untitled) (The International Journal for Scientific Research, 2026)
The study aimed to investigate the multifaceted effects of thermal stress on the motor and physiological systems of volleyball players. The research examined physiological variables (Heart Rate, Core Temperature) and kinematic indicators (Peripheral hand velocity, Take-off angle) and their relationship to the accuracy of spiking and serving. An experimental approach was applied to a sample of (12) elite players. Results indicated that elevated ambient temperatures lead to disruptions in inter-limb coordination and increased cardiorespiratory load, significantly reducing skill efficiency. The study recommended regulating training loads in hot environments and adopting external cooling strategies.